RUNX3 and T-Bet in Immunopathogenesis of Ankylosing Spondylitis—Novel Targets for Therapy? - Vecellio, Matteo; Cohen, Carla J.; Roberts, Amity R.; Wordsworth, Paul B.; Kenna, Tony J. (Frontiers in Immunology, 2019)
Susceptibility to ankylosing spondylitis (AS) is polygenic with more than 100 genes identified to date. These include HLA-B27 and the aminopeptidases (ERAP1, ERAP2 and LNPEPS), which are involved in antigen processing and presentation to T-cells, and several genes (IL23R, IL6R, STAT3, JAK2, IL1R1/2, IL12B and IL7R) involved in IL23 driven pathways of inflammation. AS is also strongly associated with polymorphisms in two transcription factors, RUNX3 and T-bet (encoded by TBX21), which are important in T-cell development and function. The influence of these genes on the pathogenesis of AS and their potential for identifying drug targets is discussed here.